Toeplitz Matrices Whose Elements Are the Coefficients of Functions with Bounded Boundary Rotation. (6th September 2016) - Radhika, V.; Sivasubramanian, S.; Murugusundaramoorthy, G.; Jahangiri, Jay M.
Abstract : LetR denote the family of functionsf ( z ) = z + ∑ n = 2 ∞ a n z n of bounded boundary rotation so thatR e f ′ ( z ) > 0 in the open unit diskU = z : z < 1 . We obtain sharp bounds for Toeplitz determinants whose elements are the coefficients of functionsf ∈ R .